Pengaruh PDRB dan Jumlah Penduduk Terhadap Tingkat Kemiskinan di Provinsi DKI Jakarta Tahun 2014-2018 - Citrawan, Mohammad Dika (Pascasarjana Universitas Muhammadiyah Mamuju, 2025)
Poverty remains one of the primary issues faced by many countries, including Indonesia. Despite economic advancements, poverty, particularly in densely populated urban areas like DKI Jakarta, continues to be a significant issue. As the capital city and economic hub, DKI Jakarta should ideally contribute to poverty alleviation. However, despite a high Gross Regional Domestic Product (GRDP), significant economic disparities still result in persistent poverty, particularly in certain districts and municipalities. This study aims to analyze the impact of GRDP and population size on poverty levels in DKI Jakarta from 2014 to 2018. By using data on GRDP and population from various districts in DKI Jakarta, this research identifies the relationship between these variables and poverty. The findings are expected to provide policy recommendations for the provincial government to design more inclusive and sustainable development strategies, thus reducing socio-economic disparities and combating poverty in the region